Desenvolvimento de um sistema computacional de monitoramento da produção do biogás por meio de sensores eletrônicos e arduino - Princival, Guilherme Cunha (2016)
Biogas is known as an alternative source of energy, comprises essentially a mixture of methane gas (CH4) and carbon dioxide (CO2). This study aimed to haracterize the biogas through a computer system (hardware and software), taking into account the two main gas composition, allowing in situ analysis, online and continuously, without human intervention in the process. For this, an experiment was conducted using electronic prototyping platform Arduino, which is fed with data from a sensor that uses non-dispersive infrared spectroscopy technology (NDIR). The results show that the system was efficient, once it is possible to monitor the concentration of CO2 and CH4 through real-time generated graphics. Moreover, it was possible to analyze the internal temperature of the anaerobic reactor through an integrated sensor to the monitoring system, which demonstrates its scalability, a desirable feature in computer systems. It was concluded also that the system detects the first signs of instability in the biodigestion process, allowing acceptable answers to establish countermeasures for its compensation.